Impacts of the Doha Development Agenda on China : The Role of Labor Markets and Complementary Education Reforms - Zhai, Fan (World Bank, Washington, DC, 2012)
The authors assess the implications of multilateral trade reforms for poverty in China. They do so by combining results from a global modeling exercise with a national CGE model that features disaggregated households in both the rural and urban sectors. They examine two trade reform scenarios: one involving global trade liberalization, and one involving possible Doha Development Agenda reforms. Using the World Bank's $2 a day poverty line, the authors find that multilateral trade reforms do in fact reduce poverty in China. The biggest reductions occur in the rural areas-largely as a result of higher prices for farm products.